APPLICATION OF THE DETROIT METHOD IN THE DISTRIBUTION OF FERRY PASSENGER MOVEMENTS IN NORTH MALUKU - Bachmid, Ryan Rinaldy R; Gaus, Abdul; Sabaruddin, Sabaruddin (JTI: Jurnal Teknik Industri, 2024)
Movement generation modelling estimates the amount of movement generated from the origin zone and attracted to the destination zone. The research aims to distribute the movement of passengers and vehicles for Ferries in North Maluku Province using the Detroit method in 7 movement distribution zones (Bastiong, Sidangoli, Rum, Sofifi, Batang Dua, Makian, and Moti). To find the distribution of ferries, the Geometric Method is used, where the value of r (growth ratio) is used as the growth factor (E) and the calculation of the distribution of movements uses the Detroit Method. The largest distribution of passengers is in the origin zone, namely Bastiong (movement 204577), in the destination zone, namely Sidangoli (movement 190621). The smallest distribution of passengers is in the origin zone, namely Batang Dua (movement 297), in the destination zone, namely Batang Dua (movement of 415). The largest distribution of vehicles is in the origin zone, namely Bastiong (movement 74828), and in the destination zone, namely Sofifi (movement 72057) and the distribution the smallest vehicle in the origin zone is Batang Dua (movement 97), and in the destination zone is Batang Dua (movement 101).